Activity-Induced Fluidization and Arrested Coalescence in Fusion of Cellular Aggregates - Ongenae, Steven; Cuvelier, Maxim; Vangheel, Jef; Ramon, Herman; Smeets, Bart (Frontiers in Physics, 2021)
At long time scales, tissue spheroids may flow or appear solid depending on their capacity to reorganize their internal structure. Understanding the relationship between intrinsic mechanical properties at the single cell level, and the tissue spheroids dynamics at the long-time scale is key for artificial tissue constructs, which are assembled from multiple tissue spheroids that over time fuse to form coherent structures. The dynamics of this fusion process are frequently analyzed in the framework of liquid theory, wherein the time scale of coalescence of two droplets is governed by its radius, viscosity and surface tension. In this work, we extend this framework to glassy or jammed cell behavior which can be observed in spheroid fusion. Using simulations of an individual-cell based model, we demonstrate how the spheroid fusion process can be steered from liquid to arrested by varying active cell motility and repulsive energy as established by cortical tension. The divergence of visco-elastic relaxation times indicates glassy relaxation near the transition toward arrested coalescence. Finally, we investigate the role of cell growth in spheroid fusion dynamics. We show that the presence of cell division introduces plasticity in the material and thereby increases coalescence during fusion.